Demographic and health attributes of the Nahua, initial contact population of the Peruvian Amazon. - Culqui, Dante R (2016)
We present the case of the Nahua population of Santa Rosa de Serjali, Peruvian Amazon's population, considered of initial contact. This population consists of human groups that for a long time decided to live in isolation, but lately have begun living a more sedentary lifestyle and in contact with Western populations. There are two fully identified initial contact groups in Peru: the Nahua and the Nanti. The health statistics of the Nahua are scarce. This study offers an interpretation of demographic and epidemiological indicators of the Nahua people, trying to identify if a certain degree of health vulnerability exists. We performed a cross sectional study, and after analyzing their health indicators, as well as the supplemental qualitative analysis of the population, brought us to conclude that in 2006, the Nahua, remained in a state of health vulnerability.